Malaysian Administrative and Modernization Unit (MAMPU) Putrajaya / Nurul Izzati Rozalan - Rozalan, Nurul Izzati (University Technology MARA Sarawak, 2016)
Malaysian Administrative Modernization and Management Planning Unit or also known as (MAMPU) was established based on a study, “Development Administration in Malaysia” conducted by Prof. John D. Montgomery and Milton J. Esman. The report acknowledged the need to upgrade professionalism in the Public Service through educational and training programmes. Based on recommendations of the report, the Development Administrative Unit (DAU) was established in 1966 to spearhead administrative reforms in the Government.